The spillover effect of work connectivity behaviors on employees' family: Based on the perspective of work-home resource model - He, Hui; Li, Dan; Zhou, Yuanyuan; Zhang, Puliang (Frontiers in Psychology, 2023)
With the rapid development of mobile communication technology, work connectivity behaviors are becoming increasingly pervasive, which has gradually attracted extensive attention from scholars and practitioners. According to the work-home resource model, we propose a theoretical model that proactive/passive work connectivity behaviors induce family harmony through self-efficacy and ego depletion, and we explore the moderating role of family support in this relationship. Based on survey data collected from 364 questionnaires using a three-wave time-lagged design, the results show that: (1) Self-efficacy plays a suppressing role in the relationship between proactive work connection behaviors and family harmony. (2) Ego depletion plays a mediating role in the relationship between passive work connectivity behaviors and family harmony; (3) Family support not only positively moderates the relationship between proactive work connectivity behaviors and self-efficacy, but also moderates the suppressing effect of proactive work connectivity behaviors on family harmony through self-efficacy; (4) Family support not only negatively moderates the relationship between passive work connectivity behaviors and ego depletion, but also moderates the mediating effect of passive work connectivity behaviors on family harmony through ego depletion. The above results can broaden our understanding of the effect of work connectivity behaviors and provide some inspiration for how to optimize the management strategy of employees’ work connectivity behaviors.